Applying the FITradeoff method for software prioritization - Aldrin Edmilson dos Santos Júnior; Pedro Sávio Menezes Cardoso; Ana Paula Henriques Gusmão de Araújo Lima (Gestão & Produção)
Abstract With the constant evolution of technology, it is noticeable that the use of software has become more common within organizations, generating more consequences for the performance of various sectors. Therefore, the increase in demand for software has also generated an increase in the availability and range of competing hardware and software, resulting in a greater diversity of products and adding complexity to decision-making within each institution on a software that meets its specific purposes. Hence, this article seeks to propose an approach to prioritizing software that a Brazilian company most needs and to do so using the FITradeoff method. The conclusions drawn from this paper indicate that it has become feasible to create a ranking of possible solutions to this problem which will serve to aid this organization to be confident in making a final decision.